Analysis of test day yield data in dairy cattle of Costa Rica - Van Arendonk, J.A.M. (1997)
General characteristics of milk production in Costa Rica: •Breeding schemes not fully established •Large variation in-Size of Herds -Management practices-Frequency of sampling-Breed types -Breeding schemes not established